القيم البلاغية في ثلاثيات البردة وانتشارها في اندونيسيا ومصر: دراسة موازنة - Wardani, Yaniah (Jurnal Adabiyah, 2023)
The rise of poets from every generation wrote poems in praise of the Prophet Muhammad SAW called Kasidah Burdah. However, due to limited information, not all literary works of the Kasidah Burdah are known. Literary scholars and researchers conclude into three great Burdah or known as "Tsulatsiyatul Burdah" written by Ka'ab bin Zuheir, Al-Bushiry and Ahmad Syauqy. This research discusses how Great Burdah works from the above poets compared from the aesthetic aspect of the beauty of the language and the aspect of its spread among Muslims in Indonesia and Egypt. The result of this study shows the Great Burdah works of the poets above have the same theme of praising the Prophet Muhammad SAW using the same Bahar but different Qafiyah with different numbers of stanzas. The differences also exist in aesthetic aspects such as diction and style of tasybih and isti'arah (metaphor) chosen by each poet. When viewed from the side of literary aesthetics, Burdah Ka'ab is more superior than others, because there are many imaginary languages and the classical language Jahily is full of tasybih, isti'arah as well as the form of symbols of women, camels and Indian swords. This is in contrast to Al-Bushiry and Ahmad Syauqi who were full of Islamic ideas using a literary language that was relatively easy to understand. Tsulatsiyatul Burdah (Great Burdah) spreads throughout Islamic countries in the world, including Indonesia and Egypt. In Indonesia, it spreads in religious assembly, Islamic boarding schools even in universities. While in Egypt it spreads in the society, sufi madrasas, universities and also in opera (arts halls). الملخص إن الشعراء عبر العصور الذين ألفوا قصيدة في مدح النبي صلى الله عليه وسلم المعروفة بـــــ " قصيدة البردة" جم غفير، ولكن بسب قصر المعلومات الموثقة الموجودة تؤثر على عجز العثور على معرفة جميع القصائد المذكورة، كما أن الخبراء والباحثين في مجال الأدب العربي استنتجوا بعد البحث إلى ثلاثيات البردة المشهورة وهي : قصيدة البردة لكعب بن زهير وقصيدة للبوصيري وقصيدة أحمد شوقي. والغرض من هذا البحث عن ثلاثيات البردة بدراسة موازنة من الناحية البلاغية وانتشارها في إندونيسيا ومصرمستخدما نظرية دراسة الأدب المقارن. ونتيجة هذا البحث أن ثلاثيات البردة تتفق في القضية التي تكلمت عنها تعنى مدح النبي صلى الله عليه وسلم كما اتفقوا على استخدام البحر البسيط مع اختلاف القوافي لكل منها وعدد الأبيات كما اختلفوا كذلك في ناحية البلاغة في اختيار العبارات والكلمات واستعمال التشبيهات والاستعارات . واذا قمنا بدراسة المقارنة الدقيقة نجد أن قصيدة كعب فاقت الاخريتين من الناحية الخيالية والمجازية واستعمال الكلمات الجاهلية القديمة والاستعارات المتنوعة مثل كنايات المرأة والجمل والسيف ونحوها. أما قصيدتي البوصيري وشوقي فاضت بالقيم الإسلامية واستعمال العبارات السهلة السلسة، كما أن ثلاثيات البردة وبوجه خاص قصيدة البردة للبوصيري قد انتشرت انتشارا واسعا في أقطار العالم بما فيه اندونيسيا ومصر ، وفي اندونيسيا انتشرت في مجالس التعليم والمعاهد الدينية والجامعات بينما في مصر انتشرت في وسط شعبها والمدارس الدينية وحلق العلم ومجالسه ومجالس شيوخهم ومجالس الطرق الصوفية ومراكز عرض الفنون والأشعار والأدب العربي مثل اوبر هوس . الكلمات الإفتتاحية: القيم البلاغية - ثلاثيات البردة - اندونيسيا - مصر Abstrak Maraknya para penyair dari setiap generasi menulis syair pujian kepada Nabi SAW yang dinamakan Kasidah Burdah. Akan tetapi karena keterbatasan informasi sehingga tidak diketahui semua karya sastra Kasidah Burdah tersebut. Para pakar dan peneliti sastra menyimpulkan menjadi tiga Burdah besar (Great Burdah) atau dikenal “Tsulatsiyatul Burdah” yaitu Burdah yang ditulis Ka’ab bin Zuheir, Al-Bushiry dan Ahmad Syauq. Penelitian ini membahas tentang sastra banding dari aspek estetika keindahan bahasanya dan bagaimana pula penyebarannya di kalangan umat Islam di Indonesia dan Mesir. Hasil dari penelitian ini, Great Burdah memiliki tema yang sama yaitu memuji Nabi SAW, dengan memakai Bahar yang sama tetapi Qafiyah berbeda dengan jumlah baitnya pun berbeda. Perbedaan pula terdapat dalam aspek estetika seperti diksi dan gaya bahasa tasybih dan isti’arah. Burdah Ka’ab lebih unggul dari yang lainnya, karena terdapat banyak ungkapan bahasa khayal dan klasik Jahily sarat dengan tasybih, isti’arah juga bentuk simbol perempuan, unta dan pedang India. Hal ini berbeda dengan Al-Bushiry dan Ahmad Syauqi yang sarat gagasannya islami dengan memakai bahasa sastra yang relatif mudah dipahami. Dari sisi penyebarannya, Tsulatsiyatul Burdah (Great Burdah) tersebar di seluruh negara di dunia termasuk di Indonesia dan Mesir. Di Indonesia tersebar di majelis ta’lim, pesantren, bahkan di perguruan tinggi. Sedangkan di Mesir banyak tersebar selain di masyarakat, madrasah sufi, perguruan tinggi, juga di tempat-tempat hiburan seperti opera (gedung pertunjukan seni). Kata Kunci: Estetika; Great Burdah; Indonesia; Mesir